2020
DOI: 10.5539/ijbm.v15n9p47
|View full text |Cite
|
Sign up to set email alerts
|

Adhocracy Culture and Strategy Implementation: An Application within Professional Bodies in Kenya

Abstract: Strategy implementation presents the most complex aspects of an organization. This study aimed at establishing the relationship between adhocracy culture and strategy implementation in professional bodies in Kenya. To accomplish the main study objective, a descriptive research design was conducted and anchored on Cameron and Quin’s theory of Competing Values Framework (CVF) supported by McKinsey 7S Framework. A sampling frame of 168 respondents from 28 active professional bodies registered with the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Strategy formulation as a part of STRP plays a significant role in influencing organisational performance in Health Establishment in Delta State. The findings of this study is in line with Njagi, Kamau and Muraguri (2020), who opined that STRP focus; the strategy formulation, the strategy selection, the organisational formation, effective communication, the height of obligation for the strategy, the harmony concerning the strategy and the association along with dissimilar sections.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Strategy formulation as a part of STRP plays a significant role in influencing organisational performance in Health Establishment in Delta State. The findings of this study is in line with Njagi, Kamau and Muraguri (2020), who opined that STRP focus; the strategy formulation, the strategy selection, the organisational formation, effective communication, the height of obligation for the strategy, the harmony concerning the strategy and the association along with dissimilar sections.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…By presenting empirical data on the relationship between STRP, strategic manoeuvrability, and company performance, this study contributes to the literature on strategic management and the theory of manoeuvres. Adhocracy Culture and Strategy Implementation: An Application within Professional Bodies in Kenya was empirically studied by Njagi, Kamau and Muraguri (2020). The study's objective was to determine the connection between Kenya's professional bodies' adhocracy culture and plan implementation.…”
Section: Stakeholders Theory Of Managementmentioning
confidence: 99%
“…Adhocracy has proven to be effective in overcoming various sectors of public problems, including health. For that, we need leaders who are able to foster a culture of adhocracy (Njagi, Ngugi Kamau, & Muraguri, 2020). The Cimahi City Government can form an adhocracy in the context of implementing population control policies in the implementation of the National Health Insurance.…”
Section: Resultsmentioning
confidence: 99%
“…The study findings indicated that adhocracy culture has positive and significant effect on effective knowledge management. Njagi, Kamau, and Muraguri, (2020), aimed at investigating the association between the adhocracy culture and strategy implementation in proffessional bodies in Kenya. The study employed descriptive research design.…”
Section: Empirical Reviewmentioning
confidence: 99%